Smoking, the xenobiotic pathway and clubfoot - Sommers, Amy (2010)
Idiopathic clubfoot is a common orthopedic birth defect that affects approximately 135,000 newborns worldwide. It is characterized by equinus, varus and adductus deformities of the ankle and foot. While numerous studies suggest a multifactorial etiology, the specific genetic and environmental components have yet to be delineated. Maternal smoking during pregnancy is the only common environmental factor consistently shown to increase the risk for clubfoot. Moreover, a positive family history of clubfoot, in conjunction with maternal smoking, increases the risk twenty-fold. These findings suggest that genetic variation in smoking metabolism (xenobiotic) genes may increase susceptibility to clubfoot. Based on this reasoning, we interrogated eight candidate genes (CYP1A1, CYP1A2, CYP1B1, CYP2A6, EPHX1, NAT2, GSTM1 and GSTT1), chosen based on their involvement in xenobiotic metabolism. Twenty-two SNPs and two null alleles in these genes were genotyped in a dataset composed of nonHispanic white and Hispanic multiplex and simplex families. Only rs1048943/CYP1A1 had significantly altered transmission in the aggregate and multiplex NHW datasets (p=0.003 and p=0.009, respectively). Perturbation of CYP1A1 can cause an increase in harmful, adduct forming metabolic intermediates. A significant interaction between EPHX1 and NAT2 was also found (p=0.007). Importantly, for CYP1A2, significant maternal (p=0.03; RR=1.24; 95% CI: 1.04–1.44) and fetal (p=0.01; RR=1.33; 95% CI: 1.13–1.54) genotypic effects were identified, suggesting that both maternal and fetal genotypes can negatively impact limb development. No association was found between maternal smoking status and variation in xenobiotic metabolism genes. Together, these results suggest that xenobiotic metabolism genes are unlikely to play a major role in clubfoot, however, perturbation of this pathway may still play a contributory role.